Legal responsibility of mining companies for agricultural land damage due to mining activities in Wasile district, East Halmahera Regency - Arsad, Jamal Hi; Faisal, Faisal; Ahmad, Imran; Budiono, Arief (Edelweiss Applied Science and Technology, 2024)
The problematic activities of mining companies towards agricultural land damage should no longer be a collegial problem, but have logical consequences for society and the environment. Furthermore, it has become a shared responsibility of humanity. Natural resources are a trigger for excessive use of environmental services. Therefore, the reason some people exploit environmental capital is not only intended to survive, but instead is based on the basis of interests alone. The purpose of this study is to analyze the form of legal responsibility of mining companies for agricultural land damage due to mining activities in Wasile District, East Halmahera Regency. The research method used in this study is the empirical legal research method, through literature studies and field studies, namely conducting interviews. Environmental protection and management requires the development of an integrated system in the form of a national policy for environmental protection and management that must be implemented in a principled and consistent manner from the center to the regions. Legal responsibilities of mining companies include: The company must ensure that environmental costs are included in the management fund including environmental preservation after mining activities are carried out.